Initial public offerings, subsequent seasoned equity offerings, and long-run performance: Evidence from IPOs in Germany - Wolfgang Bessler; Stefan Thies (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
The objective of this study is to investigate the long-run performance of initial public offerings (IPO) in Germany for the period from 1977 to 1995. Of particular interest is to examine whether underpricing and the timing of subsequent seasoned equity offerings (SEO) may help to explain why some firms have substantial positive and others have substantial negative long-run abnormal holding period returns after going public. We find significant empirical evidence that firms that raised additional funds after an IPO through a seasoned equity offering outperformed the market. There is a significant difference in returns relative to the firms that had no subsequent equity offering. A comparison of seasoned equity offerings of IPOs and of established firms suggests that the information asymmetry is more pronounced for IPO firms.
Keywords: 650